1999
DOI: 10.1034/j.1398-9995.1999.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Basophil histamine release, IgE, eosinophil counts, ECP, and EPX are related to the severity of symptoms in seasonal allergic rhinitis

Abstract: A significant relationship between the severity of allergic rhinitis and various allergic inflammatory markers was found but could account for only a minor part of the variation in the patients' evaluation of their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
4
27
2
3
Order By: Relevance
“…Other authors have found similar results [34,35]. When we compared between allergic skin and allergic conjunctivitis groups as regards peripheral blood eosinophil count we found statistically significant differences which mismatch with Winther et al [36], who found no statistically significant differences between the two groups as regards peripheral blood eosinophil count, this mismatch may be due difference in environment, population or season in which both studies were conducted. In clinical practice, peripheral blood Eosinophil counts are widely used to demonstrate the allergic etiology of disease, to monitor its clinical course and to address the choice of therapy [37].…”
Section: Discussioncontrasting
confidence: 53%
“…Other authors have found similar results [34,35]. When we compared between allergic skin and allergic conjunctivitis groups as regards peripheral blood eosinophil count we found statistically significant differences which mismatch with Winther et al [36], who found no statistically significant differences between the two groups as regards peripheral blood eosinophil count, this mismatch may be due difference in environment, population or season in which both studies were conducted. In clinical practice, peripheral blood Eosinophil counts are widely used to demonstrate the allergic etiology of disease, to monitor its clinical course and to address the choice of therapy [37].…”
Section: Discussioncontrasting
confidence: 53%
“…Atopic individuals shows significantly more IgE-mediated histamine release as compared to the non-atopic and healthy control subjects as observed by Son et al (1999). The severity of the symptoms in the allergic patients also correlated with the histamine releasibility (Winther et al, 1999).…”
Section: Article In Pressmentioning
confidence: 94%
“…Die ECP-Bestimmung eignet sich aufgrund ihrer erheblichen interindividuellen Streuung nicht zur individuellen Vorhersage. Insofern ist mithilfe von erhöhten ECP-Spiegeln weder eine diagnostische Abklärung noch eine klare Zuordnung zu einem spezifischen Krankheitsbild möglich [89]. In einzelnen Fällen kann die ECP-Bestimmung der Verlaufskontrolle bei schweren atopischen Erkrankungen dienen [90], sofern andere Verlaufsparameter nicht zur Verfügung stehen.…”
Section: Mediatoren Aus Eosinophilen Granulozytenunclassified